Are adaptive loci transferable across genomes of related species? Outlier and environmental association analyses in Alpine Brassicaceae species. Issue 6 (8th February 2013) - Zulliger, Deborah; Schnyder, Elvira; Gugerli, Felix
Abstract Local adaptation is one possible response of organisms to survive in a changing environment. However, the genetic basis of adaptation is not well understood, especially in nonmodel species. To infer recurrent patterns of local adaptation, we investigated whether the same putative adaptive loci reoccur in related species. We performed genome scans using amplified fragment length polymorphism (AFLP) markers on populations of five Alpine Brassicaceae species sampled across a wide range of environmental conditions. To identify markers potentially under directional selection, we performed outlier and environmental association analyses using a set of topo‐climatic variables available as GIS layers. Several AFLP loci showed signatures of adaptation, of which one, found in Cardamine resedifolia (Cre_P1_212.5), was associated with precipitation. We sequence‐characterized this candidate locus and genotyped single nucleotide polymorphisms (SNPs) found within this locus for all species. Testing for environmental associations of SNPs revealed the same association of this locus in Arabis alpina but not in other study species. Cumulative statistical evidence indicates that locus Cre_P1_212.5 is environmentally relevant or is linked to a gene under selection in our study range. Furthermore, the locus shows an association to the same potentially selective factor in at least one other related species. These findings help to identify trends in plant adaptation in Alpine ecosystems in response to particular environmental parameters.